Evaluation of field and flux distribution for electrical steels under unidirectional magnetization / Noor Ashikin Mohd Rashid - Noor Ashikin , Mohd Rashid (2012)
Evaluation of magnetic properties of electrical steel is vital in improving the quality of electrical machinery since it is used as magnetic cores for transformers, motors and generators. A double yoke Single Sheet Tester (SST) was modelled using two identical C-cores wound at limb side with 18 SWG copper wires in horizontal arrangement at frequency of 50 Hz. B coil and H coil sensor were used as magnetic sensor. The research was carried out using experimental analysis with the aid of Finite Element Method Magnetic (FEMM) modelling. The H-coil and B-coil sensor were positioned in the central of the sample where the uniform magnetized area can be obtained. The homogeneity of flux and field distribution of sample can be achieved at air gap length of 0.3 mm. Result indicates that yoke with dimension of (97.2x93.4x68.0) mm can generate the magnetizing field with a low reluctance flux closure path. Evaluation on specimen dimensions show that the non-uniformity of sample magnetization in overhang sample can attribute to the flux leakage between the yoke legs.The stray flux also is increased with the overhang sample. However, the so called fit in sample which is fitted nicely between the yoke end poles can be utilized to minimize the effect of stray flux. Results also indicate that the magnetic properties for both grain oriented and non-oriented silicon iron steels are influenced by the anisotropy of the material. It can be observed that the grain oriented steels have better magnetic properties than non-oriented steels. The electrical steel which has high anisotropic structures and high permeability will require less magnetic field to obtain high magnetic flux density. The differences in magnetic properties of electrical steels are due to their grain size and thickness of the sample. One-way ANOVA, T-Test and Tukey post hoc were executed at the 0.05 significance level.The statistical analysis results are in good accordance with the simulation and experimental analysis. It is statistically proven that the effectiveness of H-coil sensor is influenced by the turns of wire, N and area, A. The data also provide sufficient evidence to conclude that length of air gap and yoke’s dimension affect the magnetic measurement. It can be summarized that the evaluation of field and flux distribution for electrical steels under unidirectional magnetization are depending on anisotropy of the electrical steels and other design factors of SST such as the magnetizing method, type of sensors employed and the measuring method.